Family fast food consumption patterns and decisions among selected grade 4 students - Villavicencio, William Waldemar B. (College of Home Economics, University of the Philippines Diliman, 2018)
This study aimed to describe family fast food consumption patterns and decisions among selected Grade 4 students. The sample consisted of 30 children and parent respondents selected through cluster sampling of Grade 4 sections from U.P. Integrated School and San Vicente Elementary School. Data was gathered through a survey questionnaire focusing on fast food consumption patterns, such as frequency of visits, amount spent, preferred and frequently visited fast food outlets (FFOs) and products; and an interview on fast food consumption decisions. Descriptive statistics and content analysis was used to analyze and report data. Findings reveal that disparity in the reported monthly income between UPIS and SVES families is reflected in the differences in their fast food consumption patterns. UPIS families visit FFOs once a week, spending an average of Php 751.00 compared to Php 300.00 per once a month visit of SVES families. UPIS families also prefer and visit more FFOs but respondents from both schools have similar fast food menu preferences of chicken meals and French fries. Food consumption patterns show preference and consumption of meal and snack items that are high in fat and sugar. Parents, especially the mothers, are identified as the major decision makers but most children also play a part in the decision to eat in an FFO. Although most of the parents said that they are aware of the nutritional content of fast food products, many of them said that they were not health conscious. Thus, fewer families reported having fast food product restrictions for their children. The study shows that there is a need for increased awareness of the potential effect of these fast food consumption patterns to the long-term food choices and dietary intake of children.